2020
DOI: 10.3390/jcm9103327
|View full text |Cite
|
Sign up to set email alerts
|

The Metabolic Rearrangements of Bariatric Surgery: Focus on Orexin-A and the Adiponectin System

Abstract: The accumulation of adipose tissue represents one of the characteristics of obesity, increasing the risk of developing correlated obesity diseases such as cardiovascular disease, type 2 diabetes, cancer, and immune diseases. Visceral adipose tissue accumulation leads to chronic low inflammation inducing an imbalanced adipokine secretion. Among these adipokines, Adiponectin is an important metabolic and inflammatory mediator. It is also known that adipose tissue is influenced by Orexin-A levels, a neuropeptide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 56 publications
(85 reference statements)
2
13
0
Order By: Relevance
“…Studies have shown that the presence of LHA lesions reduces body weight and adipose tissue in rats, indicating that it may play a critical role in regulating appetite [ 56 , 57 ]. Orexin A and B are produced from orexin neurons in the LHA and are important neuropeptides that are involved in the regulation of energy balance [ 58 ]. Orexin A acts through its receptors, orexin 1 receptor (OX1R) and orexin 2 receptor (OX2R), to increase food intake as well as induce behavioral changes related to food reward [ 58 , 59 ].…”
Section: The Role Of the Nervous System In Appetite And Energy Regula...mentioning
confidence: 99%
See 3 more Smart Citations
“…Studies have shown that the presence of LHA lesions reduces body weight and adipose tissue in rats, indicating that it may play a critical role in regulating appetite [ 56 , 57 ]. Orexin A and B are produced from orexin neurons in the LHA and are important neuropeptides that are involved in the regulation of energy balance [ 58 ]. Orexin A acts through its receptors, orexin 1 receptor (OX1R) and orexin 2 receptor (OX2R), to increase food intake as well as induce behavioral changes related to food reward [ 58 , 59 ].…”
Section: The Role Of the Nervous System In Appetite And Energy Regula...mentioning
confidence: 99%
“…Orexin A and B are produced from orexin neurons in the LHA and are important neuropeptides that are involved in the regulation of energy balance [ 58 ]. Orexin A acts through its receptors, orexin 1 receptor (OX1R) and orexin 2 receptor (OX2R), to increase food intake as well as induce behavioral changes related to food reward [ 58 , 59 ]. Similar orexigenic activity is displayed by MCH, as demonstrated by experimental studies which showed that MCH gene overexpression resulted in increased food intake and obesity in mice [ 60 ].…”
Section: The Role Of the Nervous System In Appetite And Energy Regula...mentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, two independent studies have shown that in diet-induced obese mice with T2D, RYGB and VSG can down-regulate ex-pression of pro-inflammatory genes, normalize hypothalamic inflammation, and improve glucose tolerance [88,89]. Surgical intervention has been reported to increase vagal tone in rodents [90,91]. The efferent vagus nerve-based cholinergic anti-inflammatory pathway was identified to control peripheral inflammation [92].…”
Section: Hypothalamic Low-grade Inflammationmentioning
confidence: 99%